The Effectiveness of Free Health Check-Up Programs in Early Disease Detection: A Literature Review - Utami, Nur Auliah Rezky; Istiqamah, Nurul Fajriah (Journal of Scientific Insights, 2026)
Free health screening programs are one of the promotive and preventive efforts to improve public health status through early disease detection. This program aims to identify risk factors and diseases at an early stage, thus enabling faster and more effective intervention. This literature review aims to examine various studies discussing the effectiveness of free health screening programs in early disease detection in the community. This review analyzes several scientific articles on the implementation of free health screening programs in various health care facilities, with publication years ranging from 2018--2026. The research methods used in this study include quantitative research, qualitative research, mixed quantitative and qualitative methods, experimental research, and a comprehensive systematic review. The findings indicate effectiveness in early NCD detection and increased participation, despite implementation barriers. This program supports SDG 3.4 (reducing NCD deaths through prevention) and SDG 3.8 (universal health coverage), with policy recommendations for follow-up systems and technology. The review follows PRISMA and assesses the quality of studies using CASP. In addition, health screening contributes to the early detection of several diseases, including cancer, visual impairment, and HIV, thus increasing the opportunity for timely treatment. However, the program's implementation still faces several challenges, such as low community participation, limited health personnel and facilities, financial constraints, and inadequate follow-up after examinations. This program aligns with the Sustainable Development Goals (SDGs), specifically SDG 3 (Good Health and Well-Being), Target 3.4 (reducing premature mortality from non-communicable diseases through prevention and treatment), and Target 3.8 (universal health coverage). Therefore, better outreach, policy support, and strengthening of the health care system are needed to optimize the free health check-up program in efforts to prevent and control disease in the community.